Особливості формування сервовитної плівки у високонаповнених прескомпозитах - Кашицький, Віталій Павлович; Садова, Оксана Леонідівна; Люшук, Олександр Миколайович (НТУ "ХПІ", 2016)
Перспективним напрямком в сучасному трибоматеріалознавстві є розробка полімеркомпозитів, здатних до ініціювання процесів самоорганізації під час експлуатації, що призводить до формування в поверхневих шарах трибоконтакту нових стійких структур. Тому основну увагу акцентовано на особливостях виникнення ефекту вибіркового перенесення в епоксикомпозитах, наповнених порошками на основі міді та базальтовим волокном. Проаналізовано результати експериментальних досліджень та вибрано оптимальний склад епоксикомпозиту, за якого формується мідна плівка і стабілізується процес фрикційної взаємодії. Проведено хімічний аналіз трибоповерхні епоксикомпозитного матеріалу оптимального складу.

The topical direction is the development of tribotechnical composite materials based on polymer binders, in particular based on epoxy resin, which is characterized by high technology in the forming and adhesion capacity to many materials, that allows to refuse use of liquid lubricants. In this case initiation processes of self-organization, leading to the formation of new stable structures during the operation sliding bearing and contributes to stabilize the frictional parameters is perspective. The article presented the features of appearance of effect of selective transfer in epoxy composites filled by powders based on copper and basalt fibers. The results of research was analyzed and selected the optimal composition of epoxy composite, at which is formed copper film and stabilized friction process. Conducted the chemical analysis of the friction surface of epoxy composite material optimal composition and determined distribution of chemical elements in the section of epoxy composite material.
The features of formation of serfing-film in the highly filled press composites
Keywords: самоорганізація; сервовитна плівка; епоксикомпозитний материал; структура; поверхня трибоконтакту; фрикційна взаємодія; зносостійкість; self-organization; serfing-film; epoxy composite material; structure; surface of trybocontact; frictional interaction; wear resistance